Wind tunnel evaluation of novel drafting formations for an elite marathon runner - Marro, M.; Leckert, J.; Rollier, E.; Salizzoni, P.; Bailly, C. (Proceedings of the Royal Society A, 2023)
Drafting is a strategy in marathon running races that reduces the drag force acting on a designated runner. Drafting involves a formation of athletes, called pacers, running in front of (and sometimes behind) the designated runner. The present experiments evaluated complex formations involving up to seven pacers with the aim of enhancing the performances of an elite marathoner. Wind tunnel measurements with 1/10 scale articulated runner manikins were carried out. First, simple formations with one or two pacers were examined and the results were compared with previous investigations. Second, the runner formations of the Nike Breaking2 and INEOS 1:59 Challenge events whose goal was to break the 2 h marathon barrier were studied. The main finding was the identification of three complex formations of six and seven pacers that allow a drag-force reduction of about 60% with respect to a solo runner and an estimated time saving of 262 s. These results point to how it may be possible to run the fastest marathon ever.